2011
DOI: 10.1027/1618-3169/a000100
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Own-Gender Bias in Face Recognition Memory

Abstract: Women remember more female than male faces, whereas men do not seem to display an own-gender bias in face recognition memory. Why women remember female faces to a greater extent than male faces is unclear; one proposition is that women attend more to and thereby process female faces more effortfully than male faces during encoding. A manipulation that distracts attention and reduces effortful processing may therefore decrease women's own-gender bias by reducing memory for female faces relative to male faces. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
69
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(85 citation statements)
references
References 44 publications
(71 reference statements)
11
69
5
Order By: Relevance
“…The owngender advantage in face recognition is generally explained in terms of differences in interest and motivation (McKelvie, Standing, St. Jean, & Law, 1993) or perceptual expertise (Lovén, Herlitz, & Rehnman, 2011). In the present article, we investigated whether the own-gender advantage would also be evident when observers had to indicate whether a test face had been present in a previously seen set of faces, and the face could be either a true set member or a morphed average of all set members.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The owngender advantage in face recognition is generally explained in terms of differences in interest and motivation (McKelvie, Standing, St. Jean, & Law, 1993) or perceptual expertise (Lovén, Herlitz, & Rehnman, 2011). In the present article, we investigated whether the own-gender advantage would also be evident when observers had to indicate whether a test face had been present in a previously seen set of faces, and the face could be either a true set member or a morphed average of all set members.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from methodological factors, what could explain the greater averaging for owngender faces? A speculative possibility is that any greater perceptual expertise for own-gender faces (Lovén et al, 2011) would lead to an increased tendency to use shortcut strategies such as visual averaging. On this view, the owngender bias often reported for face recognition (e.g., Cross et al, 1971) and the increased averaging effects found here may both be related to a greater familiarity with own-gender faces.…”
mentioning
confidence: 99%
“…A recent meta-analysis by Herlitz and Lovén (2013) reported that women are better at recognizing faces (Hedges' g = .36), with the advantage seen primarily for female faces. Several explanations have been offered for women's advantage, such as their superior face perception (Megreya et al, 2011), greater self-reported social engagement (Sommer, Hildebrandt, Kunina-Habenicht, Schacht, & Wilhelm, 2013), increased encoding specificity of faces (Guillem & Mograss, 2005;Lovén, Herlitz, & Rehnman, 2011), and superior recognition or detection of facial expression (Hall et al, 2010). Women's face recognition may also benefit from better use of increased encoding time (McKelvie, 1981), higher circulating estradiol (Yonker et al, 2003) and own-gender faces (Herlitz & Lovén, 2013;Lewin & Herlitz, 2002;Lovén, Svärd, Ebner, Herlitz, & Fischer, 2014;Lovén et al, 2011;McKelvie, 1981;Megreya et al, 2011;Wolff, Kemter, Schweinberger, & Wiese, 2014;Wright & Sladden, 2003).…”
Section: Introductionmentioning
confidence: 94%
“…Some studies showed that females perform better than males at face processing tasks (e.g., Bowles et al, 2009;Heisz, Pottruff, & Shore, 2013;McBain, Norton, & Chen, 2009;Megreya, Bindemann, & Havard, 2011;Rehnman & Herlitz 2007;Sommer, Hildebrandt, Kunina-Habenicht, Schacht, & Wilhelm, 2013), although this female advantage was not found in all studies, in particular in the original report of the BFRT (Benton & Van Allen, 1968). This advantage is also observed sometimes only in specific conditions (see Weirich, Hoffmann, Meißner, Heinz, & Bengner, 2011), could be specific for female faces (the so-called "female own-sex bias"; see e.g., Lewin & Herlitz, 2002;Lovén, Herlitz, & Rehnman, 2011;McKelvie, Standing, St Jean, & Law, 1993;Megreya et al, 2011) with a reversed effect occasionally reported for male faces (male observers better than female observers; see e.g., McKelvie et al, 1993).…”
Section: Sex Differencesmentioning
confidence: 99%